The Rejection of the Concept of Good Taste in Kant’s Critique of the Power of Judgment - Sánchez Rodríguez, Manuel (Con-Textos Kantianos. International Journal of Philosophy, 2025)
In this article, I argue that Kant breaks with the tradition of aesthetics and with a concept inherently tied to it, namely, that of good taste or correct taste. This thinker not only acknowledges, alongside the Anglo-Saxon traditions of criticism and common sense, that it is impossible to demonstrate who possesses taste, but also maintains that there is nothing to be demonstrated in this regard. For taste does not admit of degrees, as if it were a psychological faculty or a matter of fact, such as social recognition at a given historical moment and under specific empirical circumstances. The principles of taste should not be understood as prescriptive rules; rather, they are second-order principles that do not concern how we ought to judge in each case but rather what properly constitutes the specific possibility of taste as such. What follows from the correct interpretation of these principles is a thesis that challenges the aesthetic tradition and the concept of good taste, for through its principles and the way it defines their origin, scope, and validity, it asserts that taste should not be understood as a judgment about objects or about subjects understood as an actual community.